2012
DOI: 10.2217/bmm.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Resistin, IL-6 and Lipid Profile in Elderly Patients with Ischemic Heart Disease with and Without Diabetes

Abstract: This study shows that the plasma resistin and IL-6 concentrations increased significantly in patients with ischemic heart disease with and without diabetes. This shows that there is a possible role of resistin and IL-6 in inflammatory processes, especially in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“…[ 16 ] Mean IL-6 level in the present study was similar to the level reported in a study from Pakistan in patients with CAD with diabetes and without diabetes. [ 17 ] Other studies have also reported higher level of IL-6 in patients with CAD. [ 8 16 ] Serum IL-6 levels are increased in diabetic, and hypertensive subjects[ 24 ] compared with those without these morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 ] Mean IL-6 level in the present study was similar to the level reported in a study from Pakistan in patients with CAD with diabetes and without diabetes. [ 17 ] Other studies have also reported higher level of IL-6 in patients with CAD. [ 8 16 ] Serum IL-6 levels are increased in diabetic, and hypertensive subjects[ 24 ] compared with those without these morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Highly sensitive CRP (hsCRP) and IL-6 are also associated with increased risk of all-cause mortality, and their measurement improves the ability to predict the risk of cardiovascular events. [ 8 16 17 18 19 ] Inflammation and related cytokines also interact with various metabolic factors which are related to the atherosclerotic process such as hyperglycemia, dyslipidemia, and insulin resistance (IR).…”
Section: Introductionmentioning
confidence: 99%
“…Il‑6 plasma levels increase with the severity of heart failure, and high plasma levels of Il‑6 are an important prognostic predictor in patients with congestive heart failure (Tsutamoto et al, ). Furthermore, both clinical and experimental data suggest that increased blood pressure may be a stimulus for inflammation and consecutive atherosclerotic disease, because Il‑6 levels are not only elevated in hypertensive individuals (Chae et al, ; Naya et al, ) and DOCA‐salt treated Sprague Dawly rats (Seifi et al, ), but also in patients with ischemic heart disease with and without diabetes (Yaseen et al, ). However, no data exist concerning the mechanisms leading to increased pro‐inflammatory cytokine levels due to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although these findings seem to be in contrast to our results, there are some differences in the protocols: the determination of contractility was assessed by the post rest potentiation (PRP) solely, incubation with Il‑6 was shorter and post‐incubation cell treatment was different. The absolute plasma levels of Il‑6 reported in literature are inconsistent, but in diseases like ischemic heart disease or sepsis, values of 20–140 ng/ml can be found (Scheiermann et al, ; Liao et al, ; Iba et al, ; Yaseen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yaseen et al grouped elderly patients in ischemic and nonischemic groups, as well as diabetic and nondiabetic groups. Ischemic geriatric patients in both the diabetic and nondiabetic groups had significantly higher plasma resistin levels (11). We also investigated the functional status of myocardium in stable CAD using a different method than GATED MPS.…”
Section: Discussionmentioning
confidence: 99%